Whole exome sequencing identified a pathogenic mutation of COL2A1 causing Stickler syndrome in a Vietnamese family - Ton, Nguyen Dang; Minh Chau, Pham; Thu Trang, Duong; Thi Xuan, Nguyen; Xuan Hiep, Nguyen; Hai Ha, Nguyen (Vietnam Journal of Biotechnology, 2021)
Stickler syndrome is a group of rare inherited diseases associated with abnormalities in connective tissues, specifically collagen of the eyes, ears, craniofacies, skeleton and joints. The inheritance pattern of this disease is either an autosomal dominant or an autosomal recessive based on the causative gene. Stickler syndrome is characterized by severe nearsightedness, vitreous abnormalities, distinctive facial features, hearing problems and joint anomalies. Herein, we report a case of a 37-year-old man from Vietnam suspected of Stickler syndrome, presenting a phenotype of retinal detachment and complete loss of vision, and his 3-year-old son with congenital high myopia and vitreous abnormalities. Genetic analysis using whole exome sequencing (WES) revealed a nucleotide substitution (c.C2818T/p.R940X) in exon 42 of the COL2A1 gene that was previously reported as a pathogenic variant causing Stickler syndrome. Validation of COL2A1 c.C2818T in all members of this family by using Sanger sequencing detected the presence of this pathogenic variant in the heterozygous form in the affected father and son but not in the mother and another son without any signs of a vision problem. Thus, our study contributes to not only the knowledge base of clinical and genetic aspects of Stickler syndrome in Vietnam but also the awareness of the importance of genetic counseling in patients with COL2A1 c.C2818T mutation, as well as early diagnosis and appropriate treatment to prevent serious complications, especially blindness.